2016
DOI: 10.1186/s13041-016-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory role of extranuclear apurinic/apyrimidinic endonuclease 1/redox effector factor-1 in reactive astrocytes

Abstract: Apurinic/apyrimidinic endonuclease 1 (APE1), a ubiquitous multipurpose protein, is also known as redox effector factor-1 (Ref-1). It is involved in DNA repair and redox signaling and, in turn, oxidative stress-induced neurodegeneration. Although previous studies have demonstrated that APE1/Ref-1 functions as a negative regulator of inflammatory response via several mechanisms in neuronal cells, little is known about the roles of APE1/Ref-1 in glial cells. In this study, we found that cytoplasmic APE1/Ref-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Although the exact mechanism for translocated or secreted APE1/Ref-1 is not completely understood, a few studies suggested insights into its biological functions. Altered subcellular translocation of APE1/Ref-1 in activated astrocytes regulated anti-inflammatory events [ 24 ] and recombinant APE1/Ref-1 showed anti-inflammatory activity by suppressing pro-inflammatory molecules in endothelial cells [ 23 ]. Because APE1/Ref-1 is increased and activated under the conditions like reactive oxygen species, ischemia/reperfusion injury, hypoxia or inflammation, its elevation in myocarditis may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism for translocated or secreted APE1/Ref-1 is not completely understood, a few studies suggested insights into its biological functions. Altered subcellular translocation of APE1/Ref-1 in activated astrocytes regulated anti-inflammatory events [ 24 ] and recombinant APE1/Ref-1 showed anti-inflammatory activity by suppressing pro-inflammatory molecules in endothelial cells [ 23 ]. Because APE1/Ref-1 is increased and activated under the conditions like reactive oxygen species, ischemia/reperfusion injury, hypoxia or inflammation, its elevation in myocarditis may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) including 10% fetal bovine serum, 2 mmol/L glutamine and 100 U/mL penicillin/streptomycin. The normal primary astrocytes were prepared from the neonatal rats, as described previously 58 , and cultured in Minimum Essential Media (MEM) with 10% FBS, 2 mmol/L glutamine and 100 U/mL penicillin/ streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Microglia provide neurotrophic support for neurons and mainly mediate immune responses to stabilize the CNS [ 16 ]. Astrocyte-mediated neuroprotection has been proposed to be due to the limitation of neuronal death from excitotoxins and oxidants [ 17 ], maintenance energy metabolism [ 18 ], and the regulation of osmolarity for volume control [ 19 ]. Under environmental insults in the CNS, beneficial phenotypes (anti-inflammation) of M2 microglia and A2 astrocytes can be excessively stimulated and potentially switched to detrimental phenotypes (pro-inflammation) (M1 or A1, respectively) [ 20 ].…”
Section: Innate Immune Cells In the Cns—microglia And Astrocytesmentioning
confidence: 99%